2020
DOI: 10.1038/s41550-020-1172-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized filamentary gas flows feeding the young embedded cluster in Serpens South

Abstract: Observations indicate that molecular clouds are strongly magnetized, and that magnetic fields influence the formation of stars. A key observation supporting the conclusion that molecular clouds are significantly magnetized is that the orientation of their internal structure is closely related to that of the magnetic field. At low column densities the structure aligns parallel with the field, whereas at higher column densities, the gas structure is typically oriented perpendicular to magnetic fields, with a tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 56 publications
9
51
0
Order By: Relevance
“…13 and 14). This trend has also been found recently towards the G33.92+0.11 (Wang et al 2020) and Serpens South (Pillai et al 2020) hubfilament systems. This finding suggests that the sub-filaments may be formed orthogonal to the ambient B-field and then merged with the ridge, forming a clump-hub structure, due to, e.g., shock compression events, interstellar turbulence, or under the gravitational attraction by the ridge itself.…”
Section: The B-field Structure Of a High-mass Star Forming Hub-filamesupporting
confidence: 79%
“…13 and 14). This trend has also been found recently towards the G33.92+0.11 (Wang et al 2020) and Serpens South (Pillai et al 2020) hubfilament systems. This finding suggests that the sub-filaments may be formed orthogonal to the ambient B-field and then merged with the ridge, forming a clump-hub structure, due to, e.g., shock compression events, interstellar turbulence, or under the gravitational attraction by the ridge itself.…”
Section: The B-field Structure Of a High-mass Star Forming Hub-filamesupporting
confidence: 79%
“…If the material were infalling on to the Ridge/Hot Core region, this would be similar to the behaviour seen on much larger size scales in hub-filament systems (e.g. Pillai et al 2020), where magnetic fields are seen to run along filaments of material infalling on to the central hub. The reordered field representing outflowing material is more difficult to physically motivate, as the most likely cause of such a gas outflow would be the BN/KL explosion, with which our observed polarization geometry is not consistent.…”
Section: Discussion Of Grain Alignment In the Anomalous Region/forksupporting
confidence: 55%
“…In addition, the relative orientation also depends on the characteristics of the environment and the scale such as those of cores or clumps (Zhang et al 2014;Hull et al 2017;Alina et al 2019). Recently Pillai et al (2020) reported a discovery of a change of the relative orientation from perpendicular to parallel with increasing density in the open cluster in the Serpens south cloud using Sofia HAWC+ data with sub-arcminute resolution. This is a step forward in confirming the paradigm of the relative orientation between matter and magnetic fields in molecular clouds.…”
Section: Discussionmentioning
confidence: 99%